Digital Divide Analysis in the Implementation of Educational Technology in Elementary Schools - Adi Nur Ali; M. Kholil Ridwan; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to conduct an in-depth analysis of the digital divide in the implementation of educational technology at the elementary school level, using a case study of SDN 1 Jadimulya as a representative rural school with limited resources. This study used a qualitative approach with a case study design to gain a comprehensive understanding of the digital landscape, not only in terms of infrastructure availability but also the quality of technology utilization and the subjects' experiences. Data were collected through in-depth interviews with teachers and principals, observations of the learning process, and documentation studies, then analyzed thematically. The results indicate a digital divide at two main levels. The First Level Gap appears significant, characterized by limited physical infrastructure, unstable electricity supply, and weak internet connections that hinder the functionality of ICT devices. This condition is exacerbated by the Second Level Gap, namely the low digital literacy competency of teachers and students. The majority of teachers have not yet optimally mastered Technological Pedagogical Content Knowledge (TPACK), so the use of ICT tends to be substitutive and not pedagogically integrated. The impact of this condition is stagnant learning quality, low student learning outcomes, and increasing educational inequality between rural and urban schools. Therefore, this study recommends intervention policies focused on sustainable digital infrastructure development and structured teacher capacity-building programs to comprehensively address the digital divide.